JARINGAN KOMUNIKASI KOPERASI 64 BAHARI SURABAYA DALAM PENGELOLAAN HASIL LAUT - Nugraheni, Yuli; Widyaningrum, Anastasia Yuni (Linimasa : Jurnal Ilmu Komunikasi, 2021)
In the management of the Koperasi 64 Bahari, communication problems become an important problem because this cooperative consists of many members who interact with each other without standard arrangements. The nature of communication is informal. Many things must be communicated clearly because they relate to the mass marine processing products. Not all the members have good communication skills. So this research was conducted to observe the communication network of Koperasi 64 Bahari members, where members interact with each other to share the information until they reach an understanding regarding marine product management which consists of the fishing process, the processing of catches, and the marketing of marine products. This success cannot be separated from the network that was formed in the organization. The use of a communication network analysis model ensures that the relationships and roles will be reflected through the existing information patterns and communication network elements. By knowing the roles and patterns of communication of each member of the cooperative, communication will run effectively and the objectives of the cooperative will be achieved. This study aims to determine the communication network at Koperasi 64 Bahari Surabaya. This study describes the process of forming a communication network that begins with two-way communication then develops into reciprocal communication so that it can form a converged communication model. This study uses a network analysis method, which aims to assist researchers in making relationship maps through matrices and sociograms. Through the sociogram the role of existing networks can be seen. This study results the roles that appear in the marine product management process network show there are five roles that are formed, namely Components, Clicks, Cutpoints, Bridges and Hubs. Keywords: Communication Network, Koperasi 64 Bahari